Evaluation of different calcium grain sizes in laying hens diet (2016)
The calcium grain size is important for absorption efficiency and calcification of the egg, especially when the bird’s feeding decreases. In recent years, several studies have evaluated the effect of different calcium grain sizes on the feeding of laying hens; however, the results are controversial. This research evaluates the effect of particle size on the posture rate, feed intake, egg weight, and feed conversion. 120 Hy-line White 90 weeks old laying hens, randomly distributed, received 4 treatments, each one with different calcium particle size: T1 =less than 1 mm, T2=3 mm, T3=6 mm, and T4=9 mm. Each treatment was repeated 10 times with 3 birds per experimental unit. The posture percentage showed a quadratic effect, with the percentage increasing as the particle size increased until T3; however, T4 was the treatment with the lowest posture percentage and feed intake. Although there were no significant differences between treatments for egg weight, feed conversion had the lowest value with T4. In conclusion, particle sizes of 3 mm and 6 mm have no adverse effects on animal performance parameters in 90 weeks old laying hens.